Tyrosine Kinase Inhibitors; an Approach for Targeted Cancer Therapies-A Review - Shrivastav, Arpita; Shrivastava, Neeraj (International Journal of Livestock Research, 2020)
Targeted cancer therapies include drugs which target specific molecules involved in the growth of cancer cells. These therapies comprise of monoclonal antibodies that attack cell surface receptors, apoptosis-inducing drugs, angiogenesis inhibitors and enzyme inhibitors that enter cells and inhibit critical cell enzymes. Tyrosine kinase inhibitors are synthetic agents that inhibit signal transduction pathways and interfere with activation of enzymes tyrosine kinase in cancer cells. They compete for the ATP binding site of protein tyrosine kinase and reduce tyrosine kinase phosphorylation, thereby inhibiting cancer cell production. So even if the tumour is not getting reduced, its out-of-control growth has found to be changed. This may give regular chemo for a better chance to work. Slowing or stopping out-of-control growth may also help people live longer, even without adding other drugs. These drugs have made great progress in the treatment of cancer, but the problem of acquired resistance is still unavoidable, restricting the treatment of cancer. Currently, Thirteen tyrosine kinase inhibitors have been approved by Food and Drug Administration. Among them Imatinib, Masitinib, Pazopanib and Toceranib are used for the veterinary purpose Proper dosage regimens, defining of type of cancers and combination with the standard therapeutics are some of the challenges yet to be worked on.